‘Covid-Islands’ and ‘Covid-Archipelagos’ - Andrew Halliday (Svetovi)
During the global Covid-19 pandemic, households, communities and regions around the world were faced with the hardening of borders at a variety of jurisdictional and spatial levels. These policy actions saw a sharp rise in insularisation occur as border geographies spurred insularity. The purpose of this paper is to examine this phenomenon and explore how this insular imagery took hold. Jurisdictional islanding in the form of “Covidislands” and “Covid-archipelagos” is introduced and explained as policy constructs which occurred at both micro and macro levels during the Covid-19 pandemic. This paper then examines Eastern Canada’s Covid-archipelagic “Atlantic Bubble”, constructed by the joint-islanding of the Canadian provinces of New Brunswick, Nova Scotia, Prince Edward Island, and Newfoundland and Labrador, as an illustrative case study example. The paper finishes by analysing the sociospatial and temporal dynamics of Covid-islands and Covid-archipelagos, tying to dimensions of culture, territory and society interconnected amongst prior concepts and paradigms of island understanding. Islanding in the Covid-19 era brought us back to the notion of seclusion and detachment that in a way echoes the paradigms that had already been deconstructed in the field of island studies. However, the emergence of these sociospatial island imaginaries leads us to re-think insularisation and what it meant to be insularised in the Covid-19 period.